2012
DOI: 10.1007/s00228-012-1371-x
|View full text |Cite
|
Sign up to set email alerts
|

The out-of-focus bias in drug surveillance

Abstract: PURPOSE: Existing drug safety systems with phase II and III studies and post-marketing surveillance by principle do not allow for the recognition of an important class of adverse drug reactions (ADRs). ADRs that are resistant to being detected reliably may a) appear as if they are age-related chronic diseases, which also manifest themselves in a high degree without drug treatment, b) arise in "old" drugs, c) arise during long-term application, and d) arise with the administration to frail and aged populations.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
3
0
1
Order By: Relevance
“…Non-reporting may be as frequent as 94%. 21 22 O'Beirne et al concluded from a very low report rate (<1 report per person per year) that incident reporting may be “a costly but not very effective way to study safety problems in primary care”. 23 A recent Swiss study analysed safety issues in primary care.…”
Section: Introductionmentioning
confidence: 99%
“…Non-reporting may be as frequent as 94%. 21 22 O'Beirne et al concluded from a very low report rate (<1 report per person per year) that incident reporting may be “a costly but not very effective way to study safety problems in primary care”. 23 A recent Swiss study analysed safety issues in primary care.…”
Section: Introductionmentioning
confidence: 99%
“…One further objective of observational studies is to provide Health Authorities with information on the tol-erability of medicinal products when they are used in everyday practice [32][33][34] . Investigators are encouraged to seek cooperation with Health Authorities, as information from a wide spectrum of patients is needed.…”
Section: Discussionmentioning
confidence: 99%
“…A recent report suggested that small changes in the body condition caused by medication cannot be detected from the PMS data. 13) In the present study, we calculated Q pre and Q other using AERS data. Since the AERS database is based on a spontaneous reporting system, it has a tendency of underreporting to a greater extent than the abovementioned PMS data.…”
Section: Data Sources and Study Limitationsmentioning
confidence: 99%